2021
DOI: 10.1111/fme.12516
|View full text |Cite
|
Sign up to set email alerts
|

Parasite load of Atlantic cod Gadus morhua in the Baltic Sea assessed by the liver category method, and associations with infection density and critical condition

Abstract: Fish stock assessments require input data such as numbers and/or biomass of fish, natural and fishing mortality, growth and recruitment. These data, which are derived from the market sampling of commercial catches and from the monitoring surveys, are used to evaluate the present status of exploited fish stocks and project their future development (Jennings et al., 2001). Parasites can affect their hosts ranging from the level of the individual to the level of populations (Timi & Poulin, 2020). However, fish he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…In conclusion, the present pathological changes and inflammatory reactions of the cod liver related to the infections of C. osculatum , together with indications that the parasite grow inside the liver, supports previous studies (Buchmann & Mehrdana, 2016; Mohamed et al, 2020; Ryberg et al, 2020, 2022) suggesting that infections with C. osculatum in cod can result in reduced liver functionality and thus reduced health status, as a result of damage to the liver tissue.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, the present pathological changes and inflammatory reactions of the cod liver related to the infections of C. osculatum , together with indications that the parasite grow inside the liver, supports previous studies (Buchmann & Mehrdana, 2016; Mohamed et al, 2020; Ryberg et al, 2020, 2022) suggesting that infections with C. osculatum in cod can result in reduced liver functionality and thus reduced health status, as a result of damage to the liver tissue.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that these severely infected cod may be more susceptible to other infections. This does not have to be a direct effect of the infections with C. osculatum but can be a result of the strong association between C. osculatum infection load and nutritional condition, as cod with high C. osculatum loads generally are in a poorer nutritional condition (Horbowy et al, 2016;Ryberg et al, 2020Ryberg et al, , 2022Sokolova et al, 2018). Across taxa, including teleosts, individuals with reduced nutritional condition may experience increased susceptibility to pathogens, most likely because their immune response is compromised by their poor nutritional state (Chandra, 1997;Gulland, 1992;Johansen et al, 1997).…”
Section: Other Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the mean HSI and GSI levels of parasite-infested chub mackerel fish were significantly lower than that in healthy ones. Previous studies showed that high numbers of parasites caused destruction of organ structures and subsequent decrease in organ size (Ryberg et al, 2020;Ryberg et al, 2022). This result is in accordance with that of Ondračková et al (2010) indicating that larval parasitic nematode Raphidascaris acus decreased GSI level in infested female Neogobius kessleri.…”
Section: Discussionsupporting
confidence: 82%
“…Both the increase in EBC natural mortality and reduction in growth are likely, at least partly, associated with poor body condition and a high C . osculatum load [ 22 , 49 , 72 , 73 ]. Furthermore, the present unprecedentedly small size at maturation ( Fig 4A ), in combination with poor body condition, is expected to cause mortality due to energy costs associated with reproduction [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%